Extra storage capacity in transition metal oxide lithium-ion batteries revealed by in situ magnetometry - Li, Qiang; Li, Hongsen; Xia, Qingtao; Hu, Zhengqiang; Zhu, Yue; Yan, Shishen; Ge, Chen; Zhang, Qinghua; Wang, Xiaoxiong; Shang, Xiantao; Fan, Shuting; Long, Yunze; et al. (Nature materials, 2021)
In lithium-ion batteries (LIBs), many promising electrodes that are based on transition metal oxides exhibit anomalously high storage capacities beyond their theoretical values. Although this phenomenon has been widely reported, the underlying physicochemical mechanism in such materials remains elusive and is still a matter of debate. In this work, we use in situ magnetometry to demonstrate the existence of strong surface capacitance on metal nanoparticles, and to show that a large number of spin-polarized electrons can be stored in the already-reduced metallic nanoparticles (that are formed during discharge at low potentials in transition metal oxide LIBs), which is consistent with a space charge mechanism. Through quantification of the surface capacitance by the variation in magnetism, we further show that this charge capacity of the surface is the dominant source of the extra capacity in the Fe 3 O 4 /Li model system, and that it also exists in CoO, NiO, FeF 2 and Fe 2 N systems. The space charge mechanism revealed by in situ magnetometry can therefore be generalized to a broad range of transition metal compounds for which a large electron density of states is accessible, and provides pivotal guidance for creating advanced energy storage systems. Although some transition metal oxide-based electrodes exhibit high storage capacities beyond theoretical values, the underlying physicochemical mechanism remains elusive. Surface capacitance on metal nanoparticles involving spin-polarized electrons is now shown to be consistent with a space charge mechanism.